Plant Growth Promoting Rhizobacteria (PGPR) Akar Bambu, Kacang Hijau, dan Putri Malu untuk Meningkatkan Pertumbuhan Bintil Akar Kacang Hijau - Astija Astija; Yulisa Yulisa; Lestari Alibasyah; Vita Indri Febriani (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2022)
Plant Growth Promoting Rhizobacteria (PGPR) made from the roots of bamboo, mung bean, and putri embarrassment has not yet been applied to mung bean plants, specifically to determine its effect on the number, diameter, and quality of mung bean root nodules. Therefore, this study aims to explain the effect of PGPR fertilizer from the roots of bamboo, mung bean, and putri embarrassment on the number, diameter, and quality of nodules on mung bean (Vigna radiata L.) root nodules. The study was carried out by experiment, using a completely randomized design (CRD), which consisted of 4 treatments, namely: P0 (control) = without PGPR fertilizer; P1 = bamboo root PGPR fertilizer; P2 = green bean root PGPR fertilizer; and P3 = PGPR root shame daughter fertilizer. Each treatment was repeated 6 times. The data obtained was analyzed using the Analysis of Variance (ANOVA) which was processed using the XLSTAT 2020 program. The results showed that the PGPR fertilizer treatment from bamboo roots, mung bean roots, and embarrassed daughter roots was significantly different from the control or without PGPR. Among the three types of PGPR tested, it turned out that the PGPR from the roots of putri embarrassment had the most significant effect on the number of nodules (60.67); nodule diameter (1.91 mm); and absorbance (1.88). From these results, it is recommended that PGPR from the root of the embarrassed daughter be able to significantly increase the quantity and quality of mung bean root nodules.